Requirement Model for Circular Document Management System (CDMS) - Noraini, Omar (2005)
Defining the requirements is the first step in the system design process. It is important to determine the successful or failure of the system. Requirement model is one of the techniques used to model out the requirements. This model will give a complete view of the system and represent idea without have to build an actual system. This project aims to create a requirement model for circular document management system (CDMS) using Unified Modeling Language (UML) based document and made up the necessitate validity through the prototype. Suggestion of CDMS is to solve the problem occur in circular document management in organization. Three main phases are involved in this project to create the requirement model, which are define requirements, analyze requirement and validate requirement model. In addition, a set of analysis result of existing requirement models are produced. Based on the analysis done, requirement for CDMS are produced. Beside that, requirement model of CDMS , which is consists of use case diagram, use case specification, class diagram, interaction diagram, activity diagram and requirement list of CDMS also been created. This requirement model provides a guideline in developing others document management system by specifies a solution that is right for the user's needs.